THE PREVALENCE OF FUNGAL INFECTION IN MEDICINAL PLANTS AT NGHE AN HOSPITAL OF TRADITIONAL MEDICINE, 2019 (Vietnam Journal of Community Medicine, 2022)
Objectives: Due to poor storage conditions, a large percentage of medicinal plants are infectedwith fungi. Parasitic fungi living in herbal medicine produce toxic substances such as aflatoxin,and ochratoxin, affecting the health of users. The study was conducted in the Nghe An Hospital ofTraditional Medicine in 2019 to determine the prevalence of fungal infection and fungal compositionin medicinal herbs.Subjects and methods: Subjects of the study included medicinal plants preserved at the drugstore ofNghe An Hospital of Traditional Medicine. The study employed a descriptive experimental researchmethod in Laboratory.Results: The prevalence of fungal infection by direct KOH examination was 40.0%, of whichfilamentous fungi accounted for 92.0%, and yeast only 8.0%. The prevalence of fungal infection byculture in the Saboraud agar medium was 48.1%, of which the rate of fungal infection in Chinesemedicinal herbs was 41.1%, and in Vietnamese medicinal herbs was 62.2%. By PCR, 11 speciesof fungi were identified, of which A. niger accounted for the highest percentage of 60.0% (30/50),followed by A. tubingensis 18.0% (9/50).Conclusions: The prevalence of fungal infection in medicinal plants was as high as 48.1% with adiverse species composition (11 species). It is necessary to have appropriate preservation measuresto reduce fungal infection in medicinal plants.
Keywords: Traditional medicine, medical fungi.